Facile and scalable synthesis of 2D porous Ni/C via a salt-template assisted approach for enhanced urea oxidation reaction and energy-saving hydrogen production. (28th March 2023) - Li, Fengjiao; Zhang, Xiaoming; Liang, Shuting; Sun, Mingjuan; Zhao, Xiaolin; Chen, Haiwei; Cui, Yanhui
Abstract : Cost-effective and efficient 2D porous Ni/CS composites were synthesized by a facile and scalable NaCl template-assisted route. The optimized 4-Ni/CS composite demonstrated high performances for the UOR and urea splitting cell. Abstract : Urea splitting has gained increasing attention for energy-saving hydrogen production. The development of inexpensive, efficient and durable nanostructured electrocatalysts is highly desired to overcome the sluggish kinetics of the urea oxidation reaction (UOR). Nickel-containing materials have emerged as inexpensive and promising electrocatalysts for UOR in recent years. Herein, a series of cost-effective composites consisting of different loadings of Ni nanoparticles anchored on two-dimensional (2D) porous carbon nanosheets (denoted as Ni/CS) were fabricated for UOR via a facile and eco-friendly salt template-assisted approach. Among the prepared Ni/CS composites, the 4-Ni/CS sample with a suitable nickel loading and optimum structures exhibited the best UOR performances with a low potential of 1.369 V vs. reversible hydrogen electrode (RHE) at the current density of 10 mA cm −2 and a low Tafel slope of 39 mV dec −1 . Furthermore, an overall urea splitting cell with the optimized 4-Ni/CS as the anode catalyst delivered only 1.372 V at 10 mA cm −2, which was 200 mV lower than the pure water splitting cell. The enhanced performances of 4-Ni/CS for UOR and the urea splitting cell were mainly attributed to its larger electrocatalytic specific area, more abundant active sites and defects, and faster mass transfer. The remarkable 2D porous 4-Ni/CS electrocatalyst exhibits potential application in UOR and energy-saving hydrogen production.